Modelo de gestión administrativa para alojamientos sostenibles del circuito turístico Zapanal, cantón Pujilí provincia de Cotopaxi. - Bonilla Acurio, Gabriela Patricia (2021)
This research work proposes to develop an Administrative Management Model for sustainable accommodation in the Zapanal tourist circuit, Pujilí canton, Cotopaxi province, based on the fact that there are inadequate actions that encourage and control the operation of tourist accommodation in the sector, preventing the prolonged stay of visitors, it was also possible to show that most of the establishments are not part of an official registry. That is why an administrative management model was proposed, contemplated in three stages. The initial is associated with the recognition of the place, coordinate or integrate supply and demand. In the consolidation stage, a CAME matrix was applied; (Correct, Coping, Maintaining and Exploiting). Finally, the stage of excellence, which involves the community of the sector to seek service satisfaction in internal and external customers through communication and marketing techniques. The research was descriptive with qualitative data, the techniques used were observation and surveys applied to tourists, accommodation service providers and tourism managers. Concluding that this project seeks to contribute to an orderly development of tourist accommodation through adequate administrative management that achieves sustainability.